Reviewing Japanese writing education at universities in Indonesia, China, and South Korea - Via Luviana Dewanty; Juju Juangsih; Ghaida Farisya (Inovasi Kurikulum, 2026)
Mastery of Japanese writing (sakubun) is a crucial aspect of Japanese language learning at the university level. Diverse linguistic backgrounds, cultural contexts, and writing systems pose challenges for Japanese language learners, particularly in Asian countries such as Indonesia, China, and South Korea. This study aims to highlight the problems, differences in learning models, and the use of learning media in sakubun learning in these three countries. The research method used is a systematic literature review conducted by searching academic databases for the terms "sakubun", "university", and the names of the three countries: "Indonesia", "China", and "South Korea". The results show that the difficulties faced by Indonesian, Chinese, and South Korean students in learning sakubun stem from a lack of acquired language knowledge, grammar mastery, and vocabulary mastery. In Indonesia, Sakubun learning uses Padlet to assist students in learning Sakubun, as it offers various features that support writing activities. In sakubun learning in China, the creative response project learning model is used to monitor and evaluate students' writing, thereby maximizing their creativity. Meanwhile, in South Korea, sakubun learning uses the Project-Based Learning (PjBL) model to develop students' creativity based on their individual preferences.    Abstrak Penguasaan penulisan bahasa Jepang (sakubun) merupakan aspek penting dalam pembelajaran bahasa Jepang di tingkat universitas. Keberagaman latar belakang linguistik, konteks budaya, dan sistem penulisan yang berbeda menjadi hambatan dan tantangan bagi para pembelajar bahasa Jepang, khususnya di negara-negara Asia seperti Indonesia, Cina, dan Korea Selatan. Penelitian ini bertujuan untuk menyoroti permasalahan, perbedaan model pembelajaran, serta penggunaan media pembelajaran dalam pembelajaran sakubun di tiga negara tersebut. Metode penelitian yang digunakan adalah systematic literature review dengan melakukan penelusuran pada database akademik yang memuat konteks “sakubun”, “universitas”, dan nama tiga negara, yaitu “Indonesia”, “China”, dan “Korea Selatan”. Hasil penelitian menunjukkan bahwa kesulitan yang dihadapi mahasiswa Indonesia, China, dan Korea Selatan dalam pembelajaran sakubun berasal dari kurangnya pengetahuan bahasa yang diperoleh, kurangnya penguasaan tata bahasa, serta kurangnya penguasaan kosakata. Pembelajaran sakubun di Indonesia menggunakan Padlet untuk membantu mahasiswa mempelajari Sakubun karena memiliki berbagai fitur yang mengakomodasi aktivitas menulis. Dalam pembelajaran sakubun di Cina, model pembelajaran proyek respons kreatif digunakan untuk memantau dan mengevaluasi tulisan mahasiswa agar mereka dapat memaksimalkan kreativitas. Sementara itu, pembelajaran sakubun di Korea Selatan menggunakan model Pembelajaran Berbasis Proyek (PjBL) untuk mengembangkan kreativitas mahasiswa berdasarkan preferensi pribadi masing-masing. Kata Kunci: pembelajaran menulis bahasa Jepang; sakubun; tingkatan universitas